Do junior academic bioethicists have an obligation to be activists?. (28th August 2019) - Moorlock, Greg
Abstract: Activism and bioethics have enjoyed a somewhat strained relationship. In this paper, I consider activism specifically from the perspective of junior academics. I will argue that although there may be a prima facie duty for bioethicists to be activists, countervailing considerations for junior academics may mean that they, in particular, should refrain from undertaking activist activities. I will argue this on the basis of two key claims. First, I argue that activism may come at a potential cost to the academics who undertake it, and that these costs are potentially of greatest detriment to junior academics undertaking activism. Second, I argue that junior academics are likely to be less effective activists than established academics. Moreover, undertaking activism as a junior academic may prevent one from becoming an effective activist later. Finally, I will discuss the implications of this argument for activist commitments later in one's career.